Hazard or Hardship Crafting Global Norms on the Right to Refuse Unsafe Work - Hilgert, Jeffrey (An ILR Press Book, 2013)
Today, hazardous work kills 2.3 million people each year and injures millions more. Among the most compelling yet controversial forms of legal protection for workers is the right to refuse unsafe work. The rise of globalization, precarious work, neoliberal politics, attacks on unions, and the idea of individual employment rights have challenged the protection of occupational health and safety for workers worldwide. In Hazard or Hardship, Jeffrey Hilgert presents the protection of refusal rights as a moral and a human rights question.